Forward Guidance Under the Cost Channel - David Finck (Philipps-University Marburg, School of Business and Economics, 2020)
A common finding in the literature is that forward guidance cannot be credible under discretionary policy as long as the zero lower bound is an one-off event. However, this is not the case when recurring episodes of zero interest rates are possible. In this paper, we contribute to this new result and assess the sustainability of forward guidance under the cost channel. We find that forward guidance can be sustainable under the cost channel. However, we show that it is less credible compared to a standard New Keynesian model. Our results show that this finding also depends on the strength of the cost channel. Furthermore, provide evidence that ignoring the presence of a cost channel can be costly in terms of steady-state consumption.
Keywords: E12; E43; E52; E58; E61; 330; Forward Guidance; Sustainability; Cost Channel; Discretion